Electrical and Structural properties of Copper Oxide (CuO) Thin Films on Plastic Substrate Deposited by Spray Pyrolysis Technique - Faraj, Mohammad G.; Kaka, Askander K.; Omar, Halo D. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
In this paper, copper oxide (CuO) thin films were deposited on polyimide plastic substrates by spray pyrolysis technique at different temperatures from 250 to 300°C. All the deposited films were characterized by X-ray diffraction (XRD) technique, ultraviolet (UV)-visible spectrophotometer, and hall effect measurements for the investigation of structural, optical, and electrical properties. The effects of substrate temperature on the structural, optical, and electrical properties of the films were studied. The XRD results revealed that all the CuO films have a facecentered cubic structure. The crystallite grain size was calculated using Scherrer formula and it was found that at the substrate temperature of 300°C, the CuO film presented maximum crystallite grain size of about 81.2 nm. The root mean square (RMS) roughness of the films was measured by scanning tunneling microscopy. RMS was increased with the rise of temperature. The optical transmission measurements by UV-visible spectrophotometer were used to determine the energy gap of the CuO films. Results showed that the optical energy gap has decreased with increasing the substrate temperature. Hall effect measurements showed that all the films are of p-type conductivity. Depending on the substrate temperature, hall measurement showed that the electrical resistivity and carrier concentration are varied from 77.4 Ω cm to 52.7 Ω cm and from 6.3 x1015 cm-3 to 10.1 x1015 cm-3., respectively.